Exoscopic Supraorbital Keyhole Approach for Skull Base Lesions: An Institutional Experience - Chauhan, Bhanu Pratap Singh; Hedaoo, Ketan; Parihar, Vijay; Bajaj, Jitin; Ratre, Shailendra; Sinha, Mallika; Swamy, M.N.; Sharma, Mukesh; Patidar, Jayant; Yadav, Y.R. (Asian Journal of Neurosurgery, 2025)
Background In recent times, the supraorbital approach via eyebrow incision has gained tremendous popularity in targeting the anterior skull base and few middle cranial fossa lesions, over the more traditional pterional and frontotemporal approaches. However, the extremely narrow viewing angle through this approach requires frequent adjustments of the operating table and microscope for optimal visualization. Illumination via such a small opening in such deep-seated location was another limiting factor. Keeping these problems and cumbersomeness of microscope in mind, experienced surgeons gradually shifted over to purely endoscopic or endoscope-assisted supraorbital keyhole approaches. But it was also limited due to high cost, steep learning curve, and difficulties faced in blood-filled cavities. To circumvent these limitations of the microscope and endoscope, the supraorbital keyhole approach can be accomplished with an exoscope (ExSOKHA). Although various cranial procedures using exoscope have become well established in contemporary times, there is paucity of studies and literature dedicated specifically to this minimally invasive supraorbital keyhole approach using the exoscope only. Here, we aim to study the feasibility and usefulness of the exoscope in targeting skull base lesions via the supraorbital keyhole approach to determine if it can be used in learning while transitioning from the microscope to the endoscope, with the primary objective being the user friendliness of the exoscope in the SOKHA technique.Materials and Methods This prospective observational study was conducted in the department of neurosurgery over a period of 7 years. The sample size was 50. The study utilized an exoscope and support arm—2D VITOM rigid-lens telescope (Model 28095 VA, Karl Storz Endoscopy, Tuttlingen, Germany) with a 10-mm outer diameter and a shaft length of 14 cm, light source (Xenon Nova 300, Karl Storz GmBH and Co., Tuttlingen, Germany), camera head, video display monitor, and a holding arm.Results Out of 50 cases, the majority were pituitary adenomas (30%) and meningiomas (38%), with aneurysms comprising 6%; only 4 cases (8%) had inadvertent frontal sinus opening and 2 cases (4%) had postoperative cerebrospinal fluid (CSF) leak. The duration of surgery ranged from 2 to 4 hours, with the shortest being for aneurysm clipping/CSF rhinorrhea and the longest for meningioma and pituitary adenoma excision. Intraoperatively, exoscope repositioning for adjustment was required for a maximum of nine times, which significantly reduced the overall operative time. Eight cases had near total excision; the remaining tumors had complete excision and the aneurysms had complete clipping. Hospital stay ranged from 4 to 7 days, with mean intensive care unit (ICU) stay of 3 days. None of the patients had any surgical cosmetic deformity. The Glasgow Outcome Scale of all patients was good (4/5 or 5/5). Thus, ExSOKHA offered good results in terms of operative time, frequency of adjustments, completeness of excision and clipping, and recurrence. The results were also comparable for other parameters like inadvertent frontal sinus violation, postoperative CSF leak, hospital stay, cosmetic deformity, and outcome.Conclusion The exoscope is a further advancement in the telescopic system, which provides a higher focal length (250–550 mm), ergonomically superior surgery with better depth illumination in skull base lesions approached via the supraorbital keyhole approach, significantly reducing operative time and improving resection margins due to increased corner visibility and easy maneuverability. It helps learn neuroendoscopy with the familiar principles of microneurosurgery, possibly shortening the learning curves. It bridges the gap between the endoscope and the microscope as the surgery is performed while viewing the screen (as in endoscope), but without needing to take the scope inside the operative field (as in microscope), making it easier to maneuver while also limiting space occupancy.
Keywords: exoscope; microneurosurgery; neuroendoscopy; skull base lesions; SOKHA